The different effects of admission blood glucose levels on the outcomes of ST elevation myocardial infarction patients with and without diabetes - Naimeh Mesri Alamdari; Neda Lotfi Yagin; Samad Ghaffari; Neda Roshanravan; Anita Zarrintan; Majid Mobbaseri (Scientific Reports)
Abstract The effects of hyperglycemia on the prognosis of MI patients remain uncertain. This investigation evaluates the prognostic significance of hyperglycemia upon hospital admission in patients with ST-Elevation Myocardial Infarction and assesses how diabetes mellitus (DM) affects its prognostic relevance. This cross-sectional study examined data from 334 patients diagnosed with ST-segment elevation acute coronary syndrome, obtained from the Persian Cardiovascular Disease Registry. The study assessed hospital and one-year mortality as primary outcomes. Furthermore, cut-off points for blood glucose level on admission were determined and the predictive value of these cut-off values was analyzed using logistic regression analysis. In-hospital and one-year mortality rates were 22.1% and 26% for diabetic patients, and 20.2% and 24.1% for non-diabetic patients, with no substantial discrepancy between the groups (P = 0.607, P = 0.401). ROC curve analysis determined the admission blood glucose cut-off for predicting hospital mortality at 214 mg/dl in patients with diabetes (AUC = 0.66) and 148 mg/dl in patients without diabetes (AUC = 0.71). Blood glucose values was an independent factors related to in-hospital mortality, with odds ratios of 3.78 (95% CI 1.33–10.68, P = 0.012) for diabetics and 3.07 (95% CI 1.25–7.51, P = 0.014) for non-diabetics. Additionally, heightened admission glucose was correlated with greater mortality in one year in patients affected with MI irrespective of diabetes status. Blood glucose levels at admission independently predicted increased risk of mortality both during hospitalization and at one-year follow-up in patients with MI, with a notable effect on non-diabetic patients.